Long-term follow-up of disability pensioners having musculoskeletal disorders - Strand Liv I; Magnussen Liv H; Skouen Jan S; Eriksen Hege R (BMC, 2009)
Abstract Background Previously we have conducted a randomised controlled trial (RCT) to evaluate the effect of a brief cognitive behavioural program with a vocational approach aiming to return disability pensioners with back pain to work, as compared to no intervention. One year after the intervention, 10 participants (22%) who received the program and 5 (11%) in the control group reported to have entered a return to work process. The aims of this study were to evaluate long-term effects of the intervention, and compare this effect to 2 reference populations not participating in the original trial. Methods Three groups of disability pensioners were investigated: 1) Disability pensioners having back pain (n = 89) previously participating in the RCT (randomized to either a brief cognitive behavioural intervention or to a control group), 2) 342 disability pensioners having back pain, but refusing to participate in the study and 3) 449 disability pensioners having other musculoskeletal disorders than back pain. Primary outcome was return to work, defined as a reduction in payment of disability pension. Results Only 2 of 89 (2.3%) participants from the RCT had reduced disability pension at 3-years follow-up, both from the control group. None of the participants that had been in a process of returning to work after 1 year had actually gained employment at 3-years follow-up. In the 2 groups not participating in the previous RCT, only 4 (1.2%) and 8 (1.6%) had returned to work after 3 years respectively. Conclusion The number of pensioners who returned to work was negligible in all groups regardless of having participated in a cognitive behavioural intervention or not.